Autoimmune/inflammatory syndrome induced by adjuvants (Shoenfeld's syndrome) – An update. (June 2017) - Watad, A; Quaresma, M; Brown, S; Cohen Tervaert, J W; Rodríguez-Pint, I; Cervera, R; Perricone, C; Shoenfeld, Y
Autoimmune/inflammatory syndrome induced by adjuvants (ASIA) has been widely described in many studies conducted thus far. The syndrome incorporates five immune-mediated conditions, all associated with previous exposure to various agents such as vaccines, silicone implants and several others. The emergence of ASIA syndrome is associated with individual genetic predisposition, for instance those carrying HLA-DRB1*01 or HLA-DRB4 and results from exposure to external or endogenous factors triggering autoimmunity. Such factors have been demonstrated as able to induce autoimmunity in both animal models and humans via a variety of proposed mechanisms. In recent years, physicians have become more aware of the existence of ASIA syndrome and the relationship between adjuvants exposure and autoimmunity and more cases are being reported. Accordingly, we have created a registry that includes at present more than 300 ASIA syndrome cases that have been reported by different physicians worldwide, describing various autoimmune conditions induced by diverse adjuvants. In this review, we have summarized the updated literature on ASIA syndrome and the knowledge accumulated since 2013 in order to elucidate the association between the exposure to various adjuvant agents and its possible clinical manifestations. Furthermore, we especially referred to the relationship between ASIA syndrome and systemic lupus erythematosus (SLE) and antiphospholipid syndrome (APS).